Tożsamość i rola „czterech Istot żyjących” w Ap 4,6-8 - Bąk, Tomasz Bartłomiej (Verbum Vitae, 2017)
This article provides an extensive analysis of the passage from the Book of Revelation (4:6-8) devoted to the mysterious “Four Living Creatures”. These creatures are the closest to the divine throne and should be understood as non-material beings, also known as cherubs. It can be argued that their strong resemblance to animals should be interpreted as a representation of the whole universe, with its basic elements of fire (lion), earth (calf), and air (eagle). While one important basic element, that of water, seems to be missing here, we can nevertheless detect it in the affinity of one of the “Living Creatures” to man. The human face of this creature alludes to the astrological sign of Aquarius or Pisces. The ancient traditions of the Near East were undoubtedly one source of inspiration for the author of the Book of Revelation, who drew also upon themes and imagery from certain Old Testament books (primarily the Book of Ezekiel), or from various apocryphal texts (especially those of an apocalyptic nature). The “Living Creatures” in Rev 4 play a key role in the liturgical adoration of God and in stimulating the twenty-four elders to the worship of the One Sitting on the heavenly throne.